Competitive Market Embeddedness, Diversity of the Institutional Environment, and Firm Performance - Seong-Young, Kim (Management international / International Management / Gestiòn Internacional, 2019)
The impact of competitive market embeddedness on multinational enterprises’ (MNEs’) performance is examined using a sample of 53 hypermarket MNEs from 28 countries between 2007 and 2014. We found that competitive market embeddedness has a U-shaped relationship with MNE performance, and the positive effect is stronger when the coercive institutional environment of the foreign country’s market in which an MNE operates is more diverse. Our empirical findings suggest understanding the competitive market structure among multiple rivals is important for explaining the consequences of multimarket contact.